Appraising the Quality of Medical Education Research Methods: The Medical Education Research Study Quality Instrument and the Newcastle–Ottawa Scale-Education. (August 2015) - Cook, David A.; Reed, Darcy A.
Abstract : Purpose: The Medical Education Research Study Quality Instrument (MERSQI) and the Newcastle–Ottawa Scale-Education (NOS-E) were developed to appraise methodological quality in medical education research. The study objective was to evaluate the interrater reliability, normative scores, and between-instrument correlation for these two instruments. Method: In 2014, the authors searched PubMed and Google for articles using the MERSQI or NOS-E. They obtained or extracted data for interrater reliability—using the intraclass correlation coefficient (ICC)—and normative scores. They calculated between-scale correlation using Spearman rho. Results: Each instrument contains items concerning sampling, controlling for confounders, and integrity of outcomes. Interrater reliability for overall scores ranged from 0.68 to 0.95. Interrater reliability was "substantial" or better (ICC > 0.60) for nearly all domain-specific items on both instruments. Most instances of low interrater reliability were associated with restriction of range, and raw agreement was usually good. Across 26 studies evaluating published research, the median overall MERSQI score was 11.3 (range 8.9–15.1, of possible 18). Across six studies, the median overall NOS-E score was 3.22 (range 2.08–3.82, of possible 6). Overall MERSQI and NOS-E scores correlated reasonably well (rho 0.49–0.72). Conclusions: The MERSQI and NOS-E are useful, reliable, complementary tools for appraising methodological quality of medical education research. Interpretation and use of their scores should focus on item-specific codes rather than overall scores. Normative scores should be used for relative rather than absolute judgments because different research questions require different study designs.